1990
DOI: 10.1148/radiology.174.2.1688662
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy: features at transvaginal sonography.

Abstract: A retrospective review of the transvaginal sonograms of 50 women with laparoscopically confirmed ectopic pregnancy was performed to determine whether certain sonographic findings can be detected to confirm the diagnosis. Forty-seven of the 50 pregnancies were tubal. A tubal ring (a 1-3-cm mass consisting of a 2-4-mm concentric, echogenic rim of tissue surrounding a hypoechoic center) was seen in 23 of 34 (68%) ectopic pregnancies in which the fallopian tube had not ruptured, and the tubal ring could be disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(55 citation statements)
references
References 0 publications
4
49
1
1
Order By: Relevance
“…The major advantages of transvaginal ultrasonography were an accurate evaluation of adnexal texture and improve visualization of the contents of the sac, shown also by previous studies 6, 10 . As a result, more ectopic pregnancies were diagnosed while still unruptured.…”
Section: Discussionmentioning
confidence: 65%
“…The major advantages of transvaginal ultrasonography were an accurate evaluation of adnexal texture and improve visualization of the contents of the sac, shown also by previous studies 6, 10 . As a result, more ectopic pregnancies were diagnosed while still unruptured.…”
Section: Discussionmentioning
confidence: 65%
“…21 Previous sonographic studies have reported echogenic or "particulate" fluid in 25 to 57% of ectopic pregnancies. 7,16,[22][23] The higher rate in this study likely reflects the selected patient population. Although not specifically studied prior to this study, echogenic fluid has correlated with hemoperitoneum.…”
mentioning
confidence: 82%
“…TVS has proven to be an invaluable tool in the diagnosis of this condition. The typical image of heterotopic pregnancy on TVS are the presence of an intra uterine gestation with an ectopic tubal pregnancy contained an embryo 7 or a tubal ring was present in which the tube had not ruptured, an adenexal mass with a concentric echogenic rim of tissue, a gestational sac, surrounding a hypo echoic empty centre, 8 or there are no conclusive adenexal findings and the diagnosis of ectopic pregnancy may be based on ultrasound features, such as "hematoperitoneum, hematosalpinx and free fluid in the peritoneum or the pelvis e.g. in the pouch of Douglas" 9 .…”
Section: Tvs Reportmentioning
confidence: 99%